Răspunsuri

2014-11-09T18:14:27+02:00
200-18÷[372÷(3·x)-1]-28=166                                                                               200-18÷[372÷(3·x)-1]=166+28⇒194                                                                      18÷[372÷(3·x)-1]=200-194⇒6                                                                              372÷(3·x)-1=18÷6⇒3                                                                                          372÷(3·x)=3+1⇒4                                                                                              3·x=372÷4                                                                                                        3·x=93⇒x=93÷3⇒x=31
am facut verificarea este bine
sper ca ai inteles